Selenolanthionine is the major water-soluble selenium compound in the selenium tolerant plant Cardamine violifolia - Both, Eszter Borbála; Shao, Shuxun; Xiang, Jiqian; Jókai, Zsuzsa; Yin, Hongqing; Liu, Yafeng; Magyar, Anna; Dernovics, Mihály (Biochimica et biophysica acta. General subjects, 2018)
Selenium hyperaccumulation in plants often involves the synthesis of non-proteinaceous methylated selenoamino acids serving for the elimination of excess selenium from plant metabolism to protect plant homeostasis. Our study aimed at the identification of the main selenium species of the selenium hyperaccumulator plant Cardamine violifolia (Brassicaceae) that grows in the wild in the seleniferous region of Enshi, China. A sample of this plant (3.7 g Se kg−1 d.w.) was prepared with several extraction methods and the extracted selenium species were identified and quantified with liquid chromatography mass spectrometry set-ups. The Cardamine violifolia sample did not contain in considerable amount any of the organic selenium species that are often formed in hyperaccumulator plants; the inorganic selenium content (mostly as elemental selenium) accounted only for <20% of total Se. The most abundant selenium compound, accounting for about 40% of total Se was proved to be selenolanthionine, a selenium species that has never been unambiguously identified before from any selenium containing sample. The identification process was completed with chemical synthesis too. The molar ratio of lanthionine:selenolanthionine in the water extract was ca. 1:8. Finding selenolanthionine as the main organic selenium species in a plant possibly unearths a new way of selenium tolerance. This article is part of a Special Issue entitled Selenium research in biochemistry and biophysics - 200 year anniversary issue, edited by Dr. Elias Arnér and Dr. Regina Brigelius-Flohe. •Cardamine violifolia (Brassicaceae) is a novel Se-hyperaccumulator species.•This selenium hyperaccumulator plant grows in the wild in China.•The main form of selenium in this plant is selenolanthionine.•This Se-species has never been unambiguously identified before from any samples.•Chemical synthesis was also involved to prove its identity in this study.